The Effects of an Online Data-Based Decisions Professional Development for In-service Teachers of Students with Significant Disability. (September 2016) - Jimenez, Bree A.; Mims, Pamela J.; Baker, Josh
With the increase in the use of online professional development resources, especially for rural educators, this study evaluated the effects of online training modules on in-service teachers' ability to collect and use instructional progress monitoring data to make instructional decisions for students with significant disability (i.e., moderate to severe intellectual disability, autism). In this randomized control study, 29 teachers across three states participated in online data collection or data collection plus data-based decision making training. In addition, the generalization of teachers' ability to use data-based decisions with their own student outcome data were measured. Results indicated that while the modules did support teachers' acquisition of new information, they were not sufficient to carry over to applied use on their own students' data. Further discussion on the use of module-based professional development will be presented as well as how teachers in rural areas can access this information.